Identifikasi Jenis Dan Faktor Kesalahan Siswa Kelas II SDN karangwage 02 Dalam Menyelesaikan soal Pengurangan Matematika - Reskinda Ramandani; Eka Zuliana; Denni Agung Santoso (Universitas Muria Kudus, 2026)
This study aims to analyze the forms of errors made by second-grade students of SDN Karangwage 02 in solving problems involving subtraction of whole numbers. In addition, this study also identifies the factors causing these errors. Error analysis was carried out using Newman's procedure and Kastolan's categories to clarify students' obstacles in solving complex mathematical problems. This study used a qualitative descriptive method with a purposive sampling technique, involving 13 second-grade students as subjects, with data collection techniques in the form of tests, participatory observation, in-depth interviews with students and teachers, and documentation; data analysis included reduction, presentation, and drawing conclusions with technical triangulation for validity. The conclusion of the study was that students most often made errors at the process skills stage and procedural/technical errors, especially borrowing techniques, with internal-external factors as the main causes; recommendations include strengthening the concept of place value via concrete media and a supportive approach to reduce errors.